Minimum energy mobile wireless networks - Rodoplu, V.; Meng, T.H. (1998 IEEE International Conference on Communications, 1998)
We describe a distributed position-based network protocol optimized for minimum energy consumption in mobile wireless networks that support peer-to-peer communications. Given any number of randomly deployed nodes over an area, we show that a simple local optimization scheme executed at each node guarantees strong connectivity of the entire network and attains the global minimum energy solution for the stationary case. Due to its localized nature, this protocol proves to be self-reconfiguring and stays close to the minimum energy solution when applied to the case of mobile nodes. Our simulations verify its performance.